Manajemen Penyetaraan Kurikulum Pondok Pesantren Dan Sekolah Formal Dalam Meningkatkan Efektivitas Belajar Santri Di Pondok Tahfidz Modern Al-Imam Gurah Kediri - Zulkarnaen, Ogi; Supriadi , Didi; Rejokirono, Rejokirono (JURNAL MANAJEMEN PENDIDIKAN, 2026)
MANAGEMENT OF CURRICULUM EQUALIZATION OF ISLAMIC BOARDING SCHOOLS AND FORMAL SCHOOLS IN INCREASING THE LEARNING EFFECTIVENESS OF STUDENTS AT PONDOK TAHFIDZ MODERN AL-IMAM GURAH KEDIRI This study aims to describe the management of curriculum alignment between Islamic boarding schools and formal schools and its impact on student learning effectiveness at Pondok Tahfidz Modern Al-Imam, Gurah, Kediri. This research employs a qualitative approach with a case study design. Data collection was carried out through observation, in-depth interviews, documentation, and literature review, while data analysis refers to the Miles and Huberman model. The results show that: (1) Curriculum planning is arranged by aligning the pondok’s Sahla curriculum focusing on memorization, religious studies, and languages with the National Curriculum applied by the formal school; (2) Implementation is organized through proportional scheduling, material integration, and assignment of teachers according to their competencies to avoid overburdening students; (3) Supervision is carried out in an integrated manner, with follow-ups including target adjustments, additional guidance, and educator capacity building; (4) This alignment is proven effective in eliminating the dichotomy between religious and general knowledge, enabling students to achieve academic excellence while maintaining memorization quality and character. The main challenge is maintaining students’ stamina, addressed through regular coordination and continuous program adjustments.